Effect of oceanographic conditions on the winter dispersion of Eudyptes chrysocome chrysocome - Raya Rey, Andrea Nélida; Trathan, P.; Pütz, Klemens; Schiavini, Adrian Carlos Miguel (Marine Ecology Progress Series)
We used Argos satellite transmitters to monitor the movement and oceanographic habitats used by rockhopper penguins Eudyptes chrysocome chrysocome during their winter dispersal from Staten Island, Argentina, for 2002 (n = 10) and 2003 (n = 15). In both years penguins concentrated their activities to shallow and highly productive waters with temperatures ranging from 5 to 8°C. However, analysis of migration patterns, in conjunction with remotely-sensed sea surface temperature (SST) and chlorophyll a (chl a) concentration data, showed that habitat use and movement were substantially different for the 2 years. Both years were characterised by different oceanographic conditions; comparison of SST revealed colder temperatures in 2002 than the long-term average, while temperatures in 2003 were not significantly different from average conditions. The movement of rockhopper penguins differed between years: penguins migrated to the same general locations but used a larger number of foraging areas in 2002. They also spent less time travelling than in 2003. Moreover, we also found differences in adult survival or return rate and breeding success between years. Consequently, we conclude that during colder winters with more heterogeneous oceanographic conditions (e.g. 2002), penguins are better able to find enough food to achieve body condition for the following breeding season. Fil: Raya Rey, Andrea Nélida. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Trathan, P. British Antartic Survey; Reino Unido Fil: Pütz, Klemens. Antarctic Research Trust; Alemania Fil: Schiavini, Adrian Carlos Miguel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina